2022
DOI: 10.1038/s41467-022-33739-2
|View full text |Cite
|
Sign up to set email alerts
|

Viral transduction of primary human lymphoma B cells reveals mechanisms of NOTCH-mediated immune escape

Abstract: Hotspot mutations in the PEST-domain of NOTCH1 and NOTCH2 are recurrently identified in B cell malignancies. To address how NOTCH-mutations contribute to a dismal prognosis, we have generated isogenic primary human tumor cells from patients with Chronic Lymphocytic Leukemia (CLL) and Mantle Cell Lymphoma (MCL), differing only in their expression of the intracellular domain (ICD) of NOTCH1 or NOTCH2. Our data demonstrate that both NOTCH-paralogs facilitate immune-escape of malignant B cells by up-regulating PD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Recently, results from Maurizio et al. suggested that Notch signalling could facilitate immune‐escape by upregulating PD‐L1 43 . Intriguingly, GEPIA database also indicated that Notch1 level significantly correlated PD‐L1 level in KIRC (Figure 7C).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Recently, results from Maurizio et al. suggested that Notch signalling could facilitate immune‐escape by upregulating PD‐L1 43 . Intriguingly, GEPIA database also indicated that Notch1 level significantly correlated PD‐L1 level in KIRC (Figure 7C).…”
Section: Resultsmentioning
confidence: 78%
“…Recently, results from Maurizio et al suggested that Notch signalling could facilitate immune-escape by upregulating PD-L1 43. …”
mentioning
confidence: 99%
“…On the basis of our data, proliferation of CLL/MCL cells seems to be key for a successful and efficient gene editing. Moreover, using our cell coculture method, 10 we have shown a permanent protein depletion that is maintained in any offspring cell, enabling longer follow‐up downstream analyses and targeting of several candidate genes simultaneously.…”
Section: Figurementioning
confidence: 99%
“…While recently it has been demonstrated that it is possible to genetically manipulate nonactivated B cells, 9 the use of gene editing tools in malignant B cells is still elusive. Thus, to advance further in the genetic manipulation of primary malignant B cell, such as CLL and MCL, we took advantage of our cell culture system that allows the in vitro expansion of patient‐derived CLL/MCL cells for several weeks, regardless of the clinico‐biological subtype of the disease 10 . Using this cell culture system, in which primary cells are exposed to human CD40‐ligand, IL21, and BAFF secreted by murine stromal cells, we have now established a robust method for CRISPR‐Cas9 editing of patient‐derived malignant‐activated CLL/MCL cells.…”
Section: Figurementioning
confidence: 99%
“…By secreting IFN-γ, CLL cells create an anti-apoptotic autocrine loop, and Notch upregulates both the cytokine and its receptor ( 106 ). Notch1-2 signaling represses genes fundamental to antigen-processing and presentation in CLL and mantel cell lymphoma cells, reducing their immunogenicity and having a negative impact on the prognosis of patients ( 107 ). The bivalent role of this pathway is re-emphasized by the fact that Notch2-DLL1 signaling is necessary in cytolytic CD8 T cell activation through perforin and granzyme B expression ( 108 ).…”
Section: Notch2 In Chronic Lymphocytic Leukemiamentioning
confidence: 99%